Teknologi Informasi dan Komunikasi (TIK) dalam Peningkatan Ekspor UMKM: Studi Kasus UMKM dI Ex-Dolly, Kelurahan Putat Jaya, Surabaya - Kresnawati, Megahnanda Alidyan; Kusuma, Ade (Global and Policy Journal of International Relations, 2019)
ABSTRACTThe implementation of the ASEAN Economic Community (AEC) is a huge burden for the actors of micro, small and medium enterprises (MSMEs). The challenge that is felt by MSMEs is the way to increase knowledge in the use of ICTs in order to compete with other countries' products. Surabaya has a lot of MSMEs that still need to be enhanced in the utilization of ICT, some of which are MSMEs in the Putat Jaya Surabaya Village. In an effort to improve the ability of ICT experts, MSMEs in Dolly Localization exams, especially RW III Putat Jaya, need training and assistance. In addition, it is expected that this community service activity can improve knowledge and skills for MSMEs as an effort to increase human resources in Dolly's former Localization.Keywords : SMEs, Information and communication technology (ICT) DOI : https://doi.org/10.33005/jgp.v7i02.1834